Intensive Care Management of Critical and Severe SARS-CoV-2 Infection in Pregnancy: A Retrospective Observational Study - Ahmet Oğuzhan Küçük; Mehtap Pehlivanlar Küçük; Ayşegül Pehlivanlar; Olcay Ayçiçek; Ömer Demir; Funda Öztuna; Yılmaz Bülbül; Tevfik Özlü (Galenos Yayinevi, 2023)
Objective: This study examined the clinical consequences of pregnancy coexisting with severe acute respiratory syndrome coronavirus 2 in the intensive care unit (ICU). Materials and Methods: The study was designed as a retrospective observational study. After the ethical approval of the local ethics committee, the study was conducted for a period when the number of young coronavirus disease-2019 (COVID-19) cases increased in our country. The patients enrolled in the study were pregnant/puerperal patients followed up in our third-level ICU. Results: The mean age of 35 pregnant women included in the study was 29.57±4.36 years. Twenty-one of the births (80.8%) were preterm births. Twelve (34.3%) patients received invasive mechanical ventilation (IMV), and 5 (41.7%) of these patients were deceased. Twenty-six (74.3%) underwent a cesarean section (C/S). There were 5 (14.3%) patients who needed extracorporeal membrane oxygenation and 3 (8.5%) patients who needed continuous renal replacement therapy. The 28-day neonatal mortality rate for 26 births was 3.8%. The maternal mortality rate in the ICU was 14.3%. Conclusion: The preterm birth rate was high in our pregnant patients followed up in the ICU with a diagnosis of COVID-19. Because of clinical and radiological progression in pregnant women, it is difficult to indicate any gestational week in which maternal outcomes are better to undergo C/S. IMV mortality is not higher than in non-pregnant patients, so endotracheal intubation should not be avoided in appropriate patients, whether pregnancy continues or not. The absence of fully vaccinated patients in the study group revealed the protective effect of vaccination during pregnancy.